Simulation and analytical model of reliability with possible replication of transmissions in a reconfigurable multipath wireless network - Abramova, E. A.; Bogatyrev, V. A. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2025)
Methods for ensuring and evaluating the reliability of wireless reconfigurable multipath networks are considered. The fault tolerance of multipath wireless networks is maintained using a limited number of interconnected switching nodes which allow reconfiguration when traffic is redistributed through the connected path segments. The aim of the work  is to increase the reliability of transmissions in multipath wireless networks as a result of justifying the choice of route switches, taking into account the impact on the probability of packet delivery of both failures of switching nodes and combinations of various obstacles to signal propagation along a set of communication paths with the addressable node. To compare network construction solutions, a model is proposed that reflects the influence of the location of path switch nodes on transmission reliability. The study of the reliability of a wireless multipath network is based on a combination of analytical and simulation modeling. An assessment of network reliability involves its decomposition, taking into account possible combinations of failures of path switch nodes and their impact on reconfiguration capabilities as a result of switching path segments that have retained the connectivity of their constituent nodes after failures. The probability of packet loss during transmission over wireless channels is estimated as a result of simulation using OMNeT++ tools. The proposed approach makes it possible to combine estimates of the reliability of the network structure and the process of data transmission (packet delivery) through it, taking into account node failures as well as constant and changing obstacles (conditions) of signal propagation between nodes. The possibilities of increasing the reliability of wireless networks with multipath routing are analyzed as a result of optimizing the placement of a limited number of inter-path gearshift nodes. A simulation and analytical model of the reliability of wireless reconfigurable multipath networks is proposed, which takes into account failures of communication nodes and packet losses with variations in the location of physical obstacles to signal transmission between nodes when assessing the probability of packet delivery. It is shown that the choice of the location of the inter-path switching nodes significantly affects the reliability of packet delivery, while there is an optimal placement of switches, which ensures maximum transmission reliability depending on the distribution of signal transmission obstacles along the paths. The results of the study can be applied in predicting reliability and substantiating design solutions for building fault-tolerant multipath reconfigurable wireless networks. In the future, it is expected to consider more complex network topologies, taking into account the impact of reconfiguration on both reliability and packet delivery delays.